Abnormal haemoglobins in zambia. A new haemoglobin zambia α60 (E9) lysine→Asparagine. Issue 5683 (6th December 1969) - Barclay, G. P. T.; Charlesworth, Deborah; Lehmann, H.
Abstract : A survey for abnormal haemoglobins in Zambia has demonstrated Haemoglobin S—including 187 cases of sickle-cell anaemia, Haemoglobin J Oxford on one occasion, and a new Haemoglobin Zambia in four unrelated families. No evidence for β-thalassaemia was found, but Haemoglobin H disease and other evidence for α-thalassaemia were found.